Legal And Socio-Economic Issues of Islamic Banking System in Uganda: Learning From The Indonesian Experience - Muwaffiq Jufri; Paul Atagamen Aidonojie; Saiful Abdullah; Obieshi Eregbuonye; Collins Ekpenisi (Al-Mazaahib: Jurnal Perbandingan Hukum, 2026)
The development of the Islamic Banking System tends to provide an opportunity for Uganda to diversify its financial system embedded in Sharia principles. Furthermore, it suffices to state that the introduction of the Islamic banking system in Uganda is considered one of the forceful moves in attaining economic development, growth, and facilitating transactions. However, given the early stage of the Islamic banking institution in Uganda, there are legal and socio-economic issues that tend to pose challenges to the smooth operation of the Islamic Banking System. This is concerning the fact that absence of a specific regulatory framework, ambiguity or indistinctness in the current laws regulating Islamic banking, Inadequate banking infrastructure, and lack of public awareness, seem to threaten its viability, hence, the need to draw lessons from Indonesia’s well-established Islamic banking system. Hence, the study examines the legal and socio-economic issues concerning the Islamic banking system in Uganda with a view of learning from the Indonesian experience. In this regard, primary and secondary sources of material such as laws and academic literature were extensively reviewed. The data obtained were analysed through a descriptive and analytical approach. The study found that in Uganda there is no specific regulatory framework for the Islamic banking system, and the current laws on Islamic banking in Uganda are ambiguous and complex. Furthermore, the study also found that a lack of awareness of the Islamic bank's method of operation and inadequate infrastructure could affect its viability. However, in Indonesia, the Islamic Banking system has made great strides given its well-organized banking system over the years. The study further concludes and recommends proactive regulatory clarity and resolution of socio-economic challenges concerning the Islamic Banking System in Uganda learning from the Indonesia experience.